Defending Singapore Against Foreign Interference - Muhammad Faizal Abdul Rahman (2019)
Foreign interference is the invisible hand of foreign states seeking to undermine a target state’s national interests. It affects the target state from the inside by infiltrating its national institutions and people. It is a threat that smaller states like Singapore must defend against while navigating an increasingly contested world.